Implementasi Undang-Undang ITE Nomor 19 Tahun 2016 dalam Penyelesaian Masalah Ancaman Pemerasan Melalui VCS di Media Sosial: Studi Kasus Palangka Raya: Implementation of ITE Law Number 19 of 2016 in Solving the Problem of Extortion Threats via VCS on Social Media: A Case Study of Palangka Raya - Laksminarti, Laksminarti; Putri, Oktariskila Duany (Anterior Jurnal, 2025)
Nowadays, it is tough to discard the existence of technology in human life. It also affects the sexual lives of its users. One of the social phenomena that attacks the morals of Internet users is Video Call Sex (VCS). The problem arises when this activity is no longer supposed to be private but is spread to the public through social media. The recordings made into the personal collection then turned into a threat, even a tool for extortion. One real form of technological progress is the Internet. It also affects the sexual lives of its users. One of the social phenomena that attacks the morals of Internet users is Video Call Sex (VCS). The problem arises when this activity is no longer something that is supposed to be private but is spread to the public through social media. The recordings made into the personal collection then turned into a threat, even a tool for extortion. The ITE Act is expected to be the one that can address the threat of the spread of Video Call Sex (VCS) content. This study aims to see how the implementation of the ITE Law will solve the problem of extortion of threats by the distribution of video call sex content on social media in the City of Palangka Raya. The research uses qualitative descriptive methods. Data is obtained with observation and interview techniques and analyzed using Miles and Huberman models. Validation of research through credibility tests with source triangulation techniques.